2013
DOI: 10.1186/1743-8977-10-48
|View full text |Cite
|
Sign up to set email alerts
|

Rat pulmonary responses to inhaled nano-TiO2: effect of primary particle size and agglomeration state

Abstract: BackgroundThe exact role of primary nanoparticle (NP) size and their degree of agglomeration in aerosols on the determination of pulmonary effects is still poorly understood. Smaller NP are thought to have greater biological reactivity, but their level of agglomeration in an aerosol may also have an impact on pulmonary response. The aim of this study was to investigate the role of primary NP size and the agglomeration state in aerosols, using well-characterized TiO2 NP, on their relative pulmonary toxicity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 94 publications
5
58
0
2
Order By: Relevance
“…This is consistent with previous studies reporting that nanoparticle agglomerates induced substantial biological responses after phagocytosis. For example, nano-aerosols that are composed of large agglomerates (> 100 nm) are more likely to promote pulmonary clearance via phagocytosis and the acute inflammatory responses of macrophages (Noël et al, 2013). It remains to be elucidated what factors determine whether the CNT agglomerates are phagocytosed, and how the extent of the CNT agglomerate toxicity is determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous studies reporting that nanoparticle agglomerates induced substantial biological responses after phagocytosis. For example, nano-aerosols that are composed of large agglomerates (> 100 nm) are more likely to promote pulmonary clearance via phagocytosis and the acute inflammatory responses of macrophages (Noël et al, 2013). It remains to be elucidated what factors determine whether the CNT agglomerates are phagocytosed, and how the extent of the CNT agglomerate toxicity is determined.…”
Section: Discussionmentioning
confidence: 99%
“…The length and fiber diameter of each CNT itself (#1: no information; #2: mean length of 3.5 μm, fiber diameter of 30 nm, #3: mean length of 4.51 μm, fiber diameter of 150 nm, #4: mean length of 3.0 μm, fiber diameter of 10-15 nm, #5: mean length of 3.3 μm, fiber diameter of 40-50 nm) seem not to correlate with the extent of toxicity of its agglomerates in this study. The biological responses to nanoparticles reportedly depend on the dimensions and concentrations of the nanoparticle agglomerates (Gosens et al, 2010;Noël et al, 2012Noël et al, , 2013. Furthermore, recent reports have suggested that it is not only the size but also the shape that determines the extent of the toxicity (Bhattacharjee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller nanoparticles showed more widespread organ distribution (De Jong et al ., 2008). Exposure to small aggregates of TiO 2 nanoparticles produced increased oxidative stress effects and cytotoxicity than exposure to large aggregates of these nanoparticles (Noël et al ., 2013). Therefore, well‐dispersed MWCNTs might be more toxic and show more widespread organ distribution than aggregated MWCNTs, although published data have not indicated that dispersion affected the toxicity of TiO 2 nanoparticles (Kobayashi et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Zarówno aerozole SA, jak i LA nanocząstek TiO 2 z zakresu 10-30 nm indukują większe efekty prozapalne w porównaniu z kontrolą. Autorzy sugerują, że najdrobniejsze cząstki (5 nm) penetrują łatwiej do komórek, stąd większa cytotoksyczność, natomiast cząst-ki z zakresu 10-30 nm mają największą zdolność depozycji w rejonie pęcherzyków płucnych, co indukuje procesy zapalne (38).…”
Section: Narażenie Zawodoweunclassified